The genus Manota Williston (Diptera: Mycetophilidae) in Peruvian Amazonia, with description of sixteen new species and notes on local species richness - Hippa, Heikki; Kurina, Olavi; Sääksjärvi, Ilari E. (Zootaxa, 2017)
A comprehensive study of material of the worldwide fungus gnat genus Manota Williston, sampled from the Allpahuayo-Mishana National Reserve in Peruvian Amazonia, was conducted. The following 16 species are described as new: M. aligera sp. n., M. aristoseta sp. n., M. calva sp. n., M. ciliata sp. n., M. exigua sp. n., M. digitata sp. n., M. flabellata sp. n., M. iquitosensis sp. n., M. limulata sp. n., M. micella sp. n., M. minutula sp. n., M. nuda sp. n., M. parvula sp. n., M. pauloides sp. n., M. pustulosa sp. n. and M. serrulata sp. n. In addition, the following 16 species are recorded: M. acuminata Jaschhof & Hippa, 2005, M. acutistylus Jaschhof & Hippa, 2005, M. anfracta Hippa & Kurina, 2013, M. appendiculata Hippa & Kurina, 2013, M. aristata Hippa & Kurina, 2013, M. bisulca Hippa & Kurina, 2013, M. diversiseta Jaschhof & Hippa, 2005, M. iota Hippa & Kurina, 2013, M. micula Hippa & Kurina, 2013, M. papillosa Hippa & Kurina, 2013, M. paula Hippa & Kurina, 2013, M. penicillata Jaschhof & Hippa, 2005, M. pisinna Hippa & Kurina, 2013, M. quantula Hippa & Kurina, 2013, M. spinosa Jaschhof & Hippa, 2005 and M. virgata Hippa & Kurina, 2013. Altogether 67 species of Manota are now known from the Neotropical region.